2009
DOI: 10.1002/term.153
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal tracking of cells in tissue-engineered cardiac organoids

Abstract: Cardiac tissue engineering aims to create myocardial patches for repair of defective or damaged native heart muscle. The inclusion of non-myocytes in engineered cardiac tissues has been shown to improve the properties of cardiac tissue compared to tissues engineered from enriched populations of myocytes alone. While attempts to mix non-myocytes (fibroblasts, endothelial cells) with cardiomyocytes have been made, very little is understood about how the tissue properties are affected by varying the respective ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 20 publications
(49 reference statements)
0
33
0
Order By: Relevance
“…The two EC densities at the lower end of the spectrum (8% and 15%) were chosen because they were in agreement with seeding densities previously reported to support cord formation (Levenberg et al 2002, Matsumoto et al 2007, Nor et al 1999, Wright et al 2002). The value of 31% ECs served as an effective control for comparison to our previous studies (Iyer et al 2009b). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The two EC densities at the lower end of the spectrum (8% and 15%) were chosen because they were in agreement with seeding densities previously reported to support cord formation (Levenberg et al 2002, Matsumoto et al 2007, Nor et al 1999, Wright et al 2002). The value of 31% ECs served as an effective control for comparison to our previous studies (Iyer et al 2009b). …”
Section: Resultsmentioning
confidence: 99%
“…In another example using hESC-derived CMs, Murry and colleagues (Stevens et al 2009a, 2009b) created scaffold-less tissues, and Levenberg and colleagues (Caspi et al 2007, Lesman et al 2010) created tissues on porous scaffolds using CMs, ECs and mesenchymal cells such as FBs. Their work collectively points to the fact that integration of the engineered cardiac tissue with the host myocardium was enhanced in the case of tri-culture (Iyer et al 2009b, Lesman et al 2010). In those cases, the primitive vessels in the engineered tissue functionally integrated with the host coronary vasculature and enabled graft survival.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…47 Other researchers have cultured heart muscle cells (cardiomyocytes) with non-muscle cell types in matrigel-coated microchannels. 48 Compared to the simultaneous seeding of different cell types, it was found that seeding non-muscle cells to form organoids, followed by seeding of muscle cells, yielded more elongated and densely arranged cells. This led to cardiac tissues with better functionality.…”
Section: Intercellular Interactionsmentioning
confidence: 98%